The Use Of 3CM (Cool-Critical-Creative-Meaningful) Model In Blended Learning To Improve Creative Thinking Ability In Solving Mathematics Problem - Wahyudi Wahyudi; Budi Waluya; Hardi Suyitno; Isnarto Isnarto (Universitas Negeri Makassar, 2019)
This study aims to describe and test the effectiveness of 3CM learning model with blended learning to improve students' creative thinking ability in solving mathematic problems. A pre experimental design with one group pre-test post-test design pattern was applied in this study. Creative thinking ability is measured by test technique and then in triangulation with observation and interview. Students were given a test, observed when solving the problem, and interviewed based on the answers given. To see the effectiveness of 3CM learning with blended learning done with paired T test with assisted with SPSS program then triangulated with observation and interview. Based on the test results, it obtained the average pre-test 60.51 and post-test 75.96. Result of paired T tests, test got sig value. (2-tailed) 0.000 means there was a significant difference between pre-test and post-test results. It indicated that 3CM learning with blended learning effectively improves students' creative thinking ability in solving problems. This happened because learning gives students the opportunity to think systematically by beginning by criticizing the interesting contextual problems and ending with meaningful reflection with adequate learning resources both when face-to-face and online.